Pulsed Low-Intensity Focused Ultrasound (LIFU) Activation of Ovarian Follicles - Yan Xiao; Lixia Yang; Yicong Wang; Yu Wang; Yuning Chen; Wenhan Lu; Zhenle Pei; Ruonan Zhang; Yao Ye; Xiaowei Ji; Suying Liu; Xi Dong; et al. (IEEE Open Journal of Engineering in Medicine and Biology, 2024)
Objective: A biological system's internal morphological structure or function can be changed as a result of the mechanical effect of focused ultrasound. Pulsed low-intensity focused ultrasound (LIFU) has mechanical effects that might induce follicle development with less damage to ovarian tissue. The potential development of LIFU as a non-invasive method for the treatment of female infertility is being considered, and this study sought to explore and confirm that LIFU can activate ovarian follicles. Results: We found a 50% increase in ovarian weight and in the number of mature follicles on the ultrasound-stimulated side with pulsed LIFU and intraperitoneal injection of 10 IU PMSG in 10-day-old rats. After ultrasound stimulation, the PCOS-like rats had a decrease in androgen levels, restoration of regular estrous cycle and increase in the number of mature follicles and corpora lutea, and the ratio of M1 and M2 type macrophages was altered in antral follicles of PCOS-like rats, consequently promoting further development and maturation of antral follicles. Conclusion: LIFU treatment could trigger actin changes in ovarian cells, which might disrupt the Hippo signal pathway to promote follicle formation, and the mechanical impact on the ovaries of PCOS-like rats improved antral follicle development.